Changing perspectives on the Crusades - Theron, Jacques (HTS teologiese studies, 2018)
The notion and consequences of the Crusades are still influencing the modern Christian (and Muslim) pattern of thinking. These ‘holy wars’, fought by members of the Roman Catholic Church, mostly against infidels (‘unbelievers’), including the Muslims of the time, lasted for several centuries and had varied levels of success. These wars were both lauded and criticised and currently these two opposite perceptions still persist. After the background to the historical setting of the Crusades, this article provides an overview of the changing viewpoints on this movement by describing the perspectives of the most prominent authors (exponents) who aired their views on the Crusades between the 16th century and the first part of the 21st century, finding that the negative perception runs like a thread through the last five centuries.